LaCoxFe1-XO3 (0≤x≤1) spherical nanostructures prepared via ultrasonic approach as photocatalysts - Madappa C. Maridevaru (Elsevier, 2021)
To harvest the photon energy, a sequence of perovskite-type oxides of LaCoxFe1-xO3 (0 ≤x≤1) nanostructures with distinct ‘Cobalt’ doping at the position of B-site are successfully prepared via a simple ultrasonic approach as photocatalyst. The crystallinity, phase identification, microstructure, and morphology of perovskite nanocomposites were analyzed to better understand their physicochemical properties. The catalytic efficiency was assessed using Congo Red (CR) dye by visible light irradiation for 30 min. Applying terephthalic acid as a probe molecule, the formation of hydroxyl radicals during the processes was investigated. The photocatalytic efficacy was measured by varying different Co/Fe stoichiometric molar ratios and noticed the order of sequence is 0.2 > 0.6 > 0.4 > 0.8 > 0.5 > 0 > 1 after 30 min of reaction time. Finally using LaCo0.2Fe0.8O3 nanostructures, cycling studies (n = 3) were performed to determine its photostability and reusability. The photocatalytic methodology proposed in this study was discussed extensively.